Direct Activation of Bax Protein for Cancer Therapy. Issue 2 (23rd September 2015) - Liu, Zhiqing; Ding, Ye; Ye, Na; Wild, Christopher; Chen, Haiying; Zhou, Jia
Abstract: Bax, a central cell death regulator, is an indispensable gateway to mitochondrial dysfunction and a major proapoptotic member of the B‐cell lymphoma 2 (Bcl‐2) family proteins that control apoptosis in normal and cancer cells. Dysfunction of apoptosis renders the cancer cell resistant to treatment as well as promotes tumorigenesis. Bax activation induces mitochondrial membrane permeabilization, thereby leading to the release of apoptotic factor cytochrome c and consequently cancer cell death. A number of drugs in clinical use are known to indirectly activate Bax. Intriguingly, recent efforts demonstrate that Bax can serve as a promising direct target for small‐molecule drug discovery. Several direct Bax activators have been identified to hold promise for cancer therapy with the advantages of specificity and the potential of overcoming chemo‐ and radioresistance. Further investigation of this new class of drug candidates will be needed to advance them into the clinic as a novel means to treat cancer.